The Influence of Family Support on Stroke Patient Compliance in Treatment at Blud RSU Ciamis - Nurapandi, Adi; Supriadi, Dedi; Rahman, Irpan; Nopiyanti, Rifa (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2024)
Family support is an important role for the recovery of stroke patients. With family support from all sides, stroke patients will be motivated to recover. Family support is a form of affection given to loved ones so that everyone feels cared for and loved. . This form of support can be in the form of words, behavior or material. Purpose: to find out how the influence of family support on stroke patients undergoing treatment at the BLUD of RSU Ciamis. Method: The method used in this study is a quantitative method using a descriptive design and a cross-sectional research design. The sample in this study was 32 respondents in stroke patients at the BLUD of RSU Ciamis. Results: It can be explained that there is an effect of family support on stroke patient compliance in undergoing treatment at the BLUD of RSU Ciamis. Conclusion: family support for stroke patient adherence has an influence on undergoing treatment at the BLUD of RSU Ciamis.